Augmented Reality Application Of Sign Language Learning For Deaf People Based On Android - Ririn Ardiani; Muhammad Fachrie (Jurnal Info Sains : Informatika dan Sains, 2023)
Communication is the process of delivering messages from one person to another, which is done verbally or verbally and can be understood by each other. However, some people experience communication difficulties, one of which is deaf people. Deaf people are people with special needs who experience hearing and communication difficulties. This research aims to develop sign language learning resources using BISINDO and SIBI that can be helpful and interesting in learning activities. This research also aims to overcome these obstacles by designing and implementing an augmented reality application that aims to facilitate language learning interactively and educationally. In this research, augmented reality is used to visualize sign language codes through videos projected on a smartphone. This application consists of 3 menus, namely SIBI, BISINDO, and markers. The test results using Blackbox show successful results, meaning the application is as expected. The use of augmented reality in sign language learning for the deaf can increase knowledge about sign language learning.